Size distribution, sources and chemistry of ultrafine particles at Barcelona-El Prat Airport, Spain - S. Ridolfo; X. Querol; A. Karanasiou; A. Rodríguez-Luque; N. Pérez; A. Alastuey; C. Jaén; B.L. van Drooge; M. Pandolfi; M. Pedrero; F. Amato (Environment International)
The rapid expansion of the aviation sector raises concerns about air quality impacts within and around airports. Ultrafine particles (UFP, diameter < 100 nm) are of particular concern due to their potential adverse health effects. In this study, particle number concentrations (PNC), particle number size distribution (PNSD), and other ancillary pollutants such as particulate matter (PM), nitrogen oxides (NOX), black carbon (BC), sulfur dioxide (SO2), ozone (O3), carbon monoxide (CO) and benzene, as well as organic markers and trace elements (in quasi-UFP) were measured at Barcelona-El Prat Airport (80 m and 250 m from the main taxiway and runway). Comparisons were made with an urban background (UB) location, and source apportionment of PNSD was performed using Positive Matrix Factorization (PMF). PNC inside the airport was nine-fold higher than the UB, and fifteen-fold higher when considering only nucleation mode particles (< 25 nm). Six sources contributing to PNC were identified inside the airport: Taxiing (48.7 %; mode diameter = 17 nm), Industrial/Shipping (7.4 %; mode diameter = 35 nm), Diesel (3.9 %; mode diameter = 64 nm), Regional recirculation (1.1 %; mode diameter = 100 nm), Photonucleation (16.6 %; mode diameter = 13 nm) and Takeoff (18.5 %; mode diameter = 23 nm). Due to the measurement location and prevailing wind patterns, no significant contributions from landings were detected. Chemical analysis of quasi-UFP collected on Electrical Low-Pressure Impactor (ELPI + ) filters (stages 2 to 6: 17–165 nm) revealed higher concentrations (> 2-fold) of Fe, Al, Cr, Cu, Mo, Mn, Pb, Ti, and Sb at the airport compared to the UB, with Al exhibiting the most pronounced disparity. Generally, PAH levels were low at both sites, although concentrations were higher at the airport relative to the UB. Overall, this study provides a comprehensive understanding of UFP within a major European airport, identifying the different sources contributing to PNC and PNSD.